2(3-x)+7=2x-(x-4)

Simple and best practice solution for 2(3-x)+7=2x-(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3-x)+7=2x-(x-4) equation:


Simplifying
2(3 + -1x) + 7 = 2x + -1(x + -4)
(3 * 2 + -1x * 2) + 7 = 2x + -1(x + -4)
(6 + -2x) + 7 = 2x + -1(x + -4)

Reorder the terms:
6 + 7 + -2x = 2x + -1(x + -4)

Combine like terms: 6 + 7 = 13
13 + -2x = 2x + -1(x + -4)

Reorder the terms:
13 + -2x = 2x + -1(-4 + x)
13 + -2x = 2x + (-4 * -1 + x * -1)
13 + -2x = 2x + (4 + -1x)

Reorder the terms:
13 + -2x = 4 + 2x + -1x

Combine like terms: 2x + -1x = 1x
13 + -2x = 4 + 1x

Solving
13 + -2x = 4 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
13 + -2x + -1x = 4 + 1x + -1x

Combine like terms: -2x + -1x = -3x
13 + -3x = 4 + 1x + -1x

Combine like terms: 1x + -1x = 0
13 + -3x = 4 + 0
13 + -3x = 4

Add '-13' to each side of the equation.
13 + -13 + -3x = 4 + -13

Combine like terms: 13 + -13 = 0
0 + -3x = 4 + -13
-3x = 4 + -13

Combine like terms: 4 + -13 = -9
-3x = -9

Divide each side by '-3'.
x = 3

Simplifying
x = 3

See similar equations:

| 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 | | 5x-54+3x+16=180 | | 2x^2=x^2-6 | | -4y=-x+6+zy | | 16x^4+32x^3+24x^2+8x-80=0 | | tan(x)=-0.364+0.57735027 | | 6-3u=21 | | n-6=13-4 | | 5-3(2x-4)=5(4x+2)-32 |

Equations solver categories